2008
DOI: 10.1177/0040517507087675
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Cashmere Single Jersey Knitted Fabrics Blended with High and Low Crimp Superfine Merino Wool

Abstract: In this replicated experiment, we investigated the impact of cashmere in blends with superfine wools on the mechanical properties of single jersey knitted fabrics. We also investigated the relative performance of soft, low crimp/low fiber curvature superfine wool when compared with cashmere and also when compared with traditional high crimp/high fiber curvature superfine wool in pure and blended knitted fabrics. The results indicate both the cashmere blend ratio and fiber curvature/crimp of wool affected fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 4 publications
(9 reference statements)
3
40
1
Order By: Relevance
“…Fabric construction was exactly as described in earlier study (McGregor & Postle, 2008). Yarns of count R36/2 were knitted on a 23-gauge circular machine in a single jersey structure to each of three tightness factors (TFs) 14.0, 15.5 and 17.0 tex ½ /cm with loop lengths of 4.29, 3.87 and 3.53 mm, respectively.…”
Section: Spinning and Knittingmentioning
confidence: 99%
See 2 more Smart Citations
“…Fabric construction was exactly as described in earlier study (McGregor & Postle, 2008). Yarns of count R36/2 were knitted on a 23-gauge circular machine in a single jersey structure to each of three tightness factors (TFs) 14.0, 15.5 and 17.0 tex ½ /cm with loop lengths of 4.29, 3.87 and 3.53 mm, respectively.…”
Section: Spinning and Knittingmentioning
confidence: 99%
“…Fabrics were tested for 13 attributes as described in detail previously (McGregor, 2001;McGregor & Postle, 2008, 2009. Mass per unit area (g/m 2 ) was determined with sample area of 11.35 cm 2 .…”
Section: Fibre Yarn and Fabric Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the cashmere blend ratio and fiber curvature/crimp of wool affected fiber properties [18].…”
Section: Tekstil Ve Mühendismentioning
confidence: 99%
“…McGregor and Postle [2] presented a study on investigation of the effects of cashmere in blends with superfine wools on the mechanical properties of single jersey knitted fabrics. It was stated that adding cashmere fiber to superfine merino wool provides softness, smoothness, flexibility, and suppleness to the knitted fabric.…”
Section: Introductionmentioning
confidence: 99%